Consumer valuations of the quality and safety attributes of milk and meat in Kenya - Fadiga, M.L.; Makokha, S. (2014)
This study assesses the importance of the quality and safety attributes of dairy and meat products to identify strategies for value addition. It uses product profiles generated by conjoint experiments in a consumer survey applied to 287 households in Nairobi and Eldoret. The results indicate the respondents’ willingness to pay more for improved safety and quality attributes for meat and milk products, and also show that consumers value hygiene more than packaging and colour, and are willing to pay a higher premium for clean milk compared to sealed and creamy milk. They value smell more than any other attribute, given the high premium not smelly commands compared to clean, creamy or sealed package. For meat, the premium paid for each attribute varies, with the presence of an official stamp commanding the highest premium, followed by clean, soft texture and low fat content. The valuation of these attributes varies across income strata and between the two cities.